INTERACTIVE LEARNING MEDIA FOR CRITICAL AND CREATIVE THINKING SKILLS DEVELOPMENT - Rahim, Fanny Rahmatina; Sari, Silvi Yulia; Riyasni, Selma; Suherman, Dea Stivani (PILLAR OF PHYSICS EDUCATION, 2022)
The parameters of a nation's success can be evaluated by how revolution 4.0 education advances science and technology. This is also a new difficulty in the educational realm. In order to prepare for Revolution 4.0, students must have talents as provisions. Contextual learning is one way for helping students enhance their critical and creative thinking skills. Simple harmonic motion is one of the ideas that is relevant to everyday life, hence there are many contextual problems that may be handled. To enhance students' critical and creative thinking skills, the researchers developed interactive learning media focused on the concept of simple harmonic motion. The type of research was research and development (R&D) with ADDIE model. This study examined at interactive learning media oriented at critical and creative thinking skills on the concept of simple harmonic motion. The research goal was to create learning media with critical and creative thinking skills based on the simple harmonic motion concepts. The product validity was reviewed by three physics lecturer at FMIPA UNP. Product validity has an average value of 0.83 in the very valid category.